Architecture of the Past. The Museum as a Medium for Historical Narratives - Krotoszyński, Michał (Sensus Historiae, 2019)
A period of radical political change, the paradigmatic example of which is democratization, is not only a time when society has to deal with the past and construct new political order. It is also a period when the memory of the past and the new identity of the community is under development. Memorialization initiatives, such as museums, are core mechanisms in this process. The aim of the article is to present the role of the museum as a medium for historical narratives from the perspective of both transitional justice and critical museum studies. This evaluation then serves as a tool for the analysis of two well-known museums that deal with the topic of authoritarian oppression: the House of Terror in Budapest and the European Solidarity Centre in Gdansk.